Pendampingan E-Learning Berbasis Moodle Di Masa Pandemi Untuk Guru SMU/SMK Se-Jabodetabek - Dian Pratiwi; Agung Sediyono; Gatot Budi Santoso; yaifudin; Syandra Sari (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
In the current pandemic situation, learning in schools is one of the challenges for the people of Indonesia. Continuing face-to-face studies is still quite difficult to implement, and requires another safe alternative as a way out in the form of utilizing e-learning. This is what Trisakti University will try to implement in community service activities this time for high school/vocational school teachers in the form of e-learning management training, in order to improve knowledge, knowledge and skills in managing educational web content through Moodle. In its implementation, this activity is completed from the preparation stage to the evaluation and documentation stage with a period of approximately 3 months. Based on the results of the activities attended by 140 high school teachers from Vocational High Schools in Jakarta and its surroundings, it was found that 85.7% stated that they had never used Moodle as a learning medium, and 75.8% of the participants were satisfied following this training because it had provided them with knowledge and skills in making learning content on the web. So it can be concluded that this activity has been successfully implemented.